Chemically augmented malaria sporozoites display an altered immunogenic profile - Duszenko, Nikolas; van Schuijlenburg, Roos; Chevalley-Maurel, Severine; van Willigen, Danny M.; de Bes-Roeleveld, Laura; van der Wees, Stefanie; Naar, Chanel; Baalbergen, Els; Heieis, Graham; Bunschoten, Anton; Velders, Aldrik H.; Franke-Fayard, Blandine; et al. (Frontiers in Immunology, 2023)
Despite promising results in malaria-naïve individuals, whole sporozoite (SPZ) vaccine efficacy in malaria-endemic settings has been suboptimal. Vaccine hypo-responsiveness due to previous malaria exposure has been posited as responsible, indicating the need for SPZ vaccines of increased immunogenicity. To this end, we here demonstrate a proof-of-concept for altering SPZ immunogenicity, where supramolecular chemistry enables chemical augmentation of the parasite surface with a TLR7 agonist-based adjuvant (SPZ-SAS(CL307)). In vitro, SPZ-SAS(CL307) remained well recognized by immune cells and induced a 35-fold increase in production of proinflammatory IL-6 (p < 0.001). More promisingly, immunization of mice with SPZ-SAS(CL307) yielded improved SPZ-specific IFN-γ production in liver-derived NK cells (percentage IFN-γ + cells 11.1±1.8 vs. 9.4±1.5%, p < 0.05), CD4 + T cells (4.7±4.3 vs. 1.8±0.7%, p < 0.05) and CD8 + T cells (3.6±1.4 vs. 2.5±0.9%, p < 0.05). These findings demonstrate the potential of using chemical augmentation strategies to enhance the immunogenicity of SPZ-based malaria vaccines.